Pulau Pisang Light: A Non-Malaysian Lighthouse On A Malaysian Island - Rusli, MHM; Mohamad, R; Dremliuga, R (Univ Malaya, Dept Southeast Asian Studies, Fac Arts & Social Sciences, 2024)
Indexed by WOS